Skulptuur. - Soans, Hanno (Tallinn : Estonian Sculptors' Union Tallinn, 1995)
Adusk, Aili ; Eskel, Juta ; Danieljants, Rafael ; Haggi, Erika ; Jürjo, Aime ; Kangro, Tauno ; Kadarik, Margus ; Karmin, Mati ; Luik, Airi ; Kirsipuu, Tiiu ; Maarand, Tõnu ; Kolk, Ellen ; Kuld, Ilme ; Kuld, Riho ; Mölder, Ants ; Mölder, Arseni ; Mölder, Signe ; Kuulbusch, Aime ; Ojaver, Jüri ; Ojaver, Terje ; Paberit, Juhan ; Paberit, Tõnis ; Leinbock, Peeter ; Palm, Hille ; Palm, Lembit ; Seppet, Ahti ; Smidt, Tõnu ; Markelov, Georgi ; Soans, Jaak ; Taniloo-Bogatkin, Airike ; Taniloo, Endel Eduard ; Mikof, Mare ; Pärg, Rait ; Rätsep, Irina ; Tammik, Kûlli ; Starkopf, Hannes ; Teemägi, Tiina ; Zubaka, Ivan ; Tober, Elin ; Vares, Jaan ; Tolli, Lembit ; Vernik, Vergo ; Viies, Edgar ; Viitol, Erna ; Väli, Ekke
Biog. per kunstenaar
Engels
Ests
boek
Keywords: Estland; Estonia